2019
DOI: 10.1289/ehp5496
|View full text |Cite
|
Sign up to set email alerts
|

Improving and Expanding Estimates of the Global Burden of Disease Due to Environmental Health Risk Factors

Abstract: Background:The Global Burden of Disease (GBD) study, coordinated by the Institute for Health Metrics and Evaluation (IHME), produces influential, data-driven estimates of the burden of disease and premature death due to major risk factors. Expanded quantification of disease due to environmental health (EH) risk factors, including climate change, will enhance accuracy of GBD estimates, which will contribute to developing cost-effective policies that promote prevention and achieving Sustainable Development Goals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 148 publications
0
52
0
Order By: Relevance
“…These discrepancies are due to changes in population and demographic characteristics, true exposures and exposure assessment methods used and epidemiological evidence (Ostro et al 2018 ; HEI 2019 ). Recent studies discuss the status of the current risk functions, identify the key uncertainties in the current GBD estimates and recommend solutions (Pope et al 2018 ; Burnett and Cohen 2020 ; Shaffer et al 2019 ). IHME and WHO provide a unified approach to exposure assessment for BoD estimation and have agreed to produce a single GBD Study with the aim of fully unifying methods in the spirit of the WHO/IHME collaboration ( Tichenor and Sridhar 2019 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discrepancies are due to changes in population and demographic characteristics, true exposures and exposure assessment methods used and epidemiological evidence (Ostro et al 2018 ; HEI 2019 ). Recent studies discuss the status of the current risk functions, identify the key uncertainties in the current GBD estimates and recommend solutions (Pope et al 2018 ; Burnett and Cohen 2020 ; Shaffer et al 2019 ). IHME and WHO provide a unified approach to exposure assessment for BoD estimation and have agreed to produce a single GBD Study with the aim of fully unifying methods in the spirit of the WHO/IHME collaboration ( Tichenor and Sridhar 2019 ) .…”
Section: Discussionmentioning
confidence: 99%
“…BoD calculations must be interpreted carefully because their methodology can be subject to limitations (Cohen et al 2017 ; Shaffer et al 2019 ). Recent evidence has shown that apart from cardiovascular and lung diseases, metabolic and other diseases are also associated with air pollution (Thurston et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This report highlights global research showing that pollution alone kills 9 million people every year (Landrigan et al, 2017), 15 times more deaths than from all wars and violence combined. The quality of air, water, and land is diminishing in many parts of the world because of increasing global pollution (Landrigan et al, 2017;Shaffer et al, 2019), and this degradation is being borne disproportionately by poorer nations without adequate environmental protections in place for their pollutions (Myers et al, 2017). Much of this pollution has a long lifespan in the environment, and thus, if a pollution revolution occurs tomorrow, the legacy contaminants will remain in our environment for centuries (Filippelli, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To solve global problems associated with population growth, such as climate change, loss of biodiversity, and environmental pollution, a radical transformation of the economy is needed, primarily related to energy. It has been established that prolonged exposure to air pollution leads to acute respiratory inflammation, asthma attacks, and death from cardiorespiratory diseases [2,[5][6][7]. However, the global economy is still dependent on hydrocarbons and the use of fossil fuels.…”
Section: Conclusion and Further Outlookmentioning
confidence: 99%
“…Today, air pollutionboth ambient (outdoors) and household (indoors)poses the greatest health risk. Experts believe that as a result of poor air quality, one out of every nine people dies annually [2,3]. Pollution of the surrounding outdoor air alone kills about three million people each year, mainly from non-communicable diseases.…”
Section: Introductionmentioning
confidence: 99%